Investigation on Different Filters and Different Frequency Bath i for rain Computer interface with Right Hand and Left Hand imaginations - Anandanadarajah, N.; Thiruvaran, T. (My University, 2016)
For severely paralyzed people, Brain Computer Interface (BCI) is the only option to communicate. For BCI at least left hand and right hand imagination have to be identified. This paper investigates the region of frequency band and the filter type that provide significant separation between left hand and right hand imagination. For this analysis C3 and C4 channels of 59 channel system Electroencephalogram (EEG) are used. It is found that 5-1011z band of C3 and C4 provides significant separation. Further, Chebychev type H filter emphasise the separation between left hand and right hand imagination and C4 have shown higher separation than C3. Index terms - Brain Computer Interface (BCI), Electro-encephalogram (EEG), Event-Related Desynchronization (ERD), Event-Related Synchronization (ERS), Infinite Im-pulse Response (HR), Discrete Fourier Transform (DFT), Amyotrophic lateral sclerosis (ALS).